Anaerobic Methanotrophic Archaea of the ANME-2d Cluster Are Active in a Low-sulfate, Iron-rich Freshwater Sediment - Weber, Hannah S.; Habicht, Kirsten S.; Thamdrup, Bo (Frontiers in Microbiology, 2017)
ANaerobic MEthanotrophic (ANME) archaea remove the greenhouse gas methane from anoxic environments and diminish its flux to the atmosphere. High methane removal efficiencies are well documented in marine environments, whereas anaerobic oxidation of methane (AOM) was only recently indicated as an important methane sink in freshwater systems. Freshwater AOM-mediating microorganisms lack taxonomic identification and only little is known about metabolic adaptions to prevailing biogeochemical conditions. One of the first study sites providing information about AOM activity in freshwater sediment is Lake Ørn, a low-sulfate, iron-rich Danish lake. With the aim to identify freshwater AOM-mediating archaea, we incubated AOM-active anoxic, nitrate-free freshwater sediment from Lake Ørn with 13C-labeled methane (13CCH4) and 13C-labeled bicarbonate (13CDIC) and followed the assimilation of 13C into RNA by stable isotope probing. While AOM was active, 13CCH4 and probably also 13CDIC were incorporated into uncultured archaea of the Methanosarcinales-related cluster ANME-2d, whereas other known ANME lineages were not detected. This finding strongly suggests that ANME-2d archaea perform AOM coupled to sulfate and/or iron reduction and may have the capability of mixed assimilation of CH4 and DIC. ANME-2d archaea may thus play an important role in controlling methane emissions from nitrate-depleted freshwater systems.